2020
DOI: 10.1177/0300060520903216
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM2: a potential biomarker for cholangiocarcinoma

Abstract: Objective To investigate the expression of glycosphingolipids in serum and tissue from patients with cholangiocarcinoma compared with healthy controls. Methods Nanospray ionization-linear ion trap mass spectrometry (NSI-MSn) was used to demonstrate the comparative structural glycomics of glycosphingolipids in serum from patients with cholangiocarcinoma (n=15), compared with healthy controls (n = 15). GM2 expression in cholangiocarcinoma tissues (n = 60) was evaluated by immunohistochemistry. Results Eleven gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…The results suggest that aberrant expression of ceramide-metabolizing enzymes occurs in CCA. Additionally, high GCS expression in CCA is consistent with the studies on lipidomic measurements in CCA tissues, in which high levels of hexosylceramides and lactosylceramides are observed in CCA tissues, and these levels were associated with short survival of the CCA patients [ 34 , 35 ]. Up-regulation of GCS is implicated in cancer progression and multi-drug resistance, but the role of glucosylceramide breakdown (including GBA1 and GBA2) in cancer is unclear.…”
Section: Discussionsupporting
confidence: 84%
“…The results suggest that aberrant expression of ceramide-metabolizing enzymes occurs in CCA. Additionally, high GCS expression in CCA is consistent with the studies on lipidomic measurements in CCA tissues, in which high levels of hexosylceramides and lactosylceramides are observed in CCA tissues, and these levels were associated with short survival of the CCA patients [ 34 , 35 ]. Up-regulation of GCS is implicated in cancer progression and multi-drug resistance, but the role of glucosylceramide breakdown (including GBA1 and GBA2) in cancer is unclear.…”
Section: Discussionsupporting
confidence: 84%
“…Here, the authors reported on a gradual increase in GM1, GM2, GM3, GD1, and GD3 species towards malignant tumors [ 137 ]. A similar observation was reported in cholangiocarcinoma, demonstrating that the GM2 concentration was elevated in the serum of patients with cholangiocarcinoma [ 138 ]. Elevated gangliosides in cancer patients were also reported in blood samples in 73 children with high-risk neuroblastoma compared with 40 cancer-free children using LC-TMS.…”
Section: An Overview Of Current Methodologies To Characterize Gslssupporting
confidence: 84%
“…Hence, specific gangliosides are associated with certain kinds of cancer and have therefore been proposed as potential biomarkers. In a study of breast cancer patients, GM3 was found to be an excellent diagnostic marker for the luminal B breast cancer subtype [ 121 ], whereas GM2 has been proposed as a potential biomarker for cholangiocarcinoma [ 122 ]. In children with neuroblastoma, GD2 shed from tumors into the circulation was found to be a highly significant predictor of high‐risk tumors [ 123 ], while the ganglioside profile of patient‐derived melanoma cells was predictive of aggressiveness [ 124 ] and survival [ 125 ].…”
Section: Step 4: Metastasismentioning
confidence: 99%